1990
DOI: 10.5980/jpnjurol1989.81.909
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Cushing Syndrome Due to Three Distinct Adenomas of Right Adrenal

Abstract: A case is presented of a 40 y.o. female with Cushing's syndrome. Her plasma glucocorticoid values were elevated (11-deoxy-cortisol: 3.46 ng/ml, cortisol: 25.6 micrograms/dl and cortisone: 35.7 ng/ml) with loss of diurnal variation. Urine 17-OHCS value failed to b suppressed by high dose dexamethasone and was unchanged after metyrapone administration. Her plasma mineral corticoids and androgens were within normal limits. There were 3 separate tumors in the right adrenal on CT and the left adrenal had no uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Among these, the great majority of the cases were bilateral adrenocortical adenomas (Chappel, 1963;Aiba et al, 1992;Mimou et al, 1985). Only three cases of unilateral multiple adenomas have been reported in the literature written in Japanese (Yoshikawa & Yajima, 1977;Kiyohara et al, 1979;Kaneko & Ishigouoka, 1990), but none in English. When multiple adrenocortical lesions are detected in a patient with Cushing's syndrome, it is important to determine whether the lesions represent tumours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, the great majority of the cases were bilateral adrenocortical adenomas (Chappel, 1963;Aiba et al, 1992;Mimou et al, 1985). Only three cases of unilateral multiple adenomas have been reported in the literature written in Japanese (Yoshikawa & Yajima, 1977;Kiyohara et al, 1979;Kaneko & Ishigouoka, 1990), but none in English. When multiple adrenocortical lesions are detected in a patient with Cushing's syndrome, it is important to determine whether the lesions represent tumours.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that these two adenomas had different biological characteristics and the brown tumour was primarily involved in overproduction of cortisol in this patient. When analysing unilateral multiple adrenocortical lesions, approaches using immunohistochemical studies for steroidogenic enzymes, enzyme activity assays and cell culture can help to define the steroidogenesis of individual adrenocortical lesions.Unilateral multiple adrenocortical adenomas are very rare (Yoshikawa & Yajima, 1977;Kiyohara et al, 1979;Kaneko & Ishigouoka, 1990). We recently had the opportunity to examine two separate but unilateral adrenocortical adenomas in a 52year-old woman with Cushing's syndrome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theo y văn thế giới báo cáo từ năm 1977 đến nay ghi nhận khoảng 11 trường hợp hiếm gặp có đa u tuyến thượng thận cùng bên [5][6][7][8][9][10][11], đa số được báo cáo tại Nhật Bản, trong đó 3 ca có ba adenoma đều tiết cortisol hoặc aldosterone hoặc đồng tiết cả hai, 4 ca có hai u đều tiết cortisol hoặc aldosterone hoặc có một u không tiết đi kèm u có tiết aldosterone, và 4 ca có dạng nhiều adenoma vi thể cùng bên tiết aldosterone [12]. Tuy nhiên trong một nghiên cứu gần đây của tác giả Omair A Shariq và cộng sự [13], tỉ lệ mắc đa u tuyến thượng thận cùng bên khoảng 10.2% ở những bệnh nhân CANP có cắt tuyến thượng thận một bên, điều này có lẽ do y học ngày càng phát triển và công cụ chẩn đoán bệnh chính xác hơn.…”
Section: Bàn Luận Về Tần Suất Và Chẩn đOánunclassified
“…Cases of multiple neoplasms are extremely rare in these patients, with the great majority of the cases being bilateral adrenocortical adenomas. [3][4][5] Four cases of unilateral multiple adenomas have been reported in the Japanese literature, [6][7][8][9] and one in the English-language literature. 10 In this issue of Clinical and Experimental Nephrology, Okura et al 11 report that three lesions detected in the right adrenal gland of a 62-year-old woman with PA and subclinical/ preclinical Cushing's syndrome were considered to represent three different adrenocortical adenomas.…”
mentioning
confidence: 99%